2018
DOI: 10.1016/j.bbr.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the insular-striatal circuit decreases alcohol self-administration and increases sensitivity to alcohol

Abstract: Internal drug states/cues can impact drug taking, as pretreatment with a moderate to high alcohol dose (i.e., loading dose) can decrease subsequent alcohol self-administration, alcohol-seeking, and relapse-like drinking. The insular cortex (IC) is implicated in processing information about internal states and findings show that silencing the IC and its projections to the nucleus accumbens core (AcbC) enhance sensitivity to the interoceptive effects of alcohol. Therefore, the goal of the present work was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…The insula is an important neural substrate for reward and addiction (Droutman et al., ; Naqvi et al., ) and is critical for mediating cue‐induced craving that can drive drug use (Droutman et al., ; Naqvi et al., ). This is supported by rodent models of alcohol addiction, which have shown that disrupting excitatory insular‐striatal circuitry decreases alcohol self‐administration and increases sensitivity to alcohol (Jaramillo et al., ,). Decrements in FA in the vicinity of the insula in our young adult AUD sample may lead to impaired ability to detect changes in internal states such as alcohol intoxication (Berk et al., ; Migliorini et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…The insula is an important neural substrate for reward and addiction (Droutman et al., ; Naqvi et al., ) and is critical for mediating cue‐induced craving that can drive drug use (Droutman et al., ; Naqvi et al., ). This is supported by rodent models of alcohol addiction, which have shown that disrupting excitatory insular‐striatal circuitry decreases alcohol self‐administration and increases sensitivity to alcohol (Jaramillo et al., ,). Decrements in FA in the vicinity of the insula in our young adult AUD sample may lead to impaired ability to detect changes in internal states such as alcohol intoxication (Berk et al., ; Migliorini et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…However, despite its close location, AI seems to perform qualitatively different functions: AI inhibition increases drinking and self-administration, whereas OFC inhibition decreases reinstatement, but not drinking or self-administration. It is also worth noting that specific circuits within these regions may differentially contribute to seeking and use of alcohol and other reinforcers as, for example, inactivation of AI projections to nucleus accumbens actually decreased alcohol self-administration (Jaramillo et al, 2018a;Jaramillo et al, 2018b;Seif et al, 2013). In general, addressing both regional and circuit-selective differences in contributions to behavior is a key strategy going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, chemogenetic silencing of insula projections to the nucleus accumbens decreased alcohol self-administration and potentiated the subjective, or interoceptive, effects of alcohol in rats (10)(11)(12). Analogous behavioral studies in humans showed that heavy drinkers attempted to earn more alcohol drinks than light drinkers under threat of shock and exhibited greater connectivity between the insula and nucleus accumbens, a brain region involved in motivation and reward, when viewing shock-predictive alcohol cues (3).…”
Section: Introductionmentioning
confidence: 98%